2020
DOI: 10.3390/pharmaceutics12111081
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Disaggregates Prion Fibrils and Decreases Fibril-Induced Cytotoxicity and Oxidative Stress

Abstract: Transmissible spongiform encephalopathies (TSEs) are fatal neurodegenerative diseases caused by misfolding and aggregation of prion protein (PrP). Previous studies have demonstrated that quercetin can disaggregate some amyloid fibrils, such as amyloid β peptide (Aβ) and α-synuclein. However, the disaggregating ability is unclear in PrP fibrils. In this study, we examined the amyloid fibril-disaggregating activity of quercetin on mouse prion protein (moPrP) and characterized quercetin-bound moPrP fibrils by ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…As reported previously, quercetin disaggregated mature prion fibrils ( Yu and Lee, 2020 ). We examined the stable binding of quercetin ( Figure 3A ) to fPrP 170–229 by a 162 ns MD simulation of quercetin-fPrP 170–229 complexes.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As reported previously, quercetin disaggregated mature prion fibrils ( Yu and Lee, 2020 ). We examined the stable binding of quercetin ( Figure 3A ) to fPrP 170–229 by a 162 ns MD simulation of quercetin-fPrP 170–229 complexes.…”
Section: Resultssupporting
confidence: 83%
“…The binding of COMPs increases loop and helix contents in fPrP 170−229 ( Figures 7B, C ). Quercetin is shown to be highly effective for prion fibril treatment ( Yu and Lee, 2020 ). Herein, we found that quercetin binding decreases strand content and increases loop and helix contents in fPrP 170−229 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a series of analysis above, we gained six signi cant compounds, keampferol concentrated in Baishao(Peony) ,quercetin and isorhamnetin were enriched in Danpi(Moutan Cortex),cerevisterol and 3,5-Dihydroxyergosta-7,22-dien-80-one were found in Fuling(Poria), glycosmisic acid existed in Guizhi(Cinnamomi Ramulus). Keampferol and quercetin always appeared at the same time due to the familiar effectiveness in antiin ammatory, antioxidation and proapoptosis [36][37][38][39].In a network study of TCM treating cancer-related pain [40], quercetin and kaempferol also worked as very important compounds, which could regulate the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)pathways to achieve the purpose of antitumor and alleviating pain.It might provide evidences for the effect of quercetin and kaempferol ameliorating the pain of menstruation. Cerevisterol and 3,5-Dihydroxyergosta-7,22-dien-80-one were usually isolated and identi ed from the mycelia, which could treat in ammatory diseases by targeting an MAPK, NF-κB, AP-1, and Nrf2-mediated HO-1 signaling cascade [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with flavones demonstrated properties against Aβ 42 aggregation in vitro [ 25 , 26 ]. In many cases, the anti-aggregation potential is evaluated via measurement of amyloidophilic dye thioflavin-T (ThT) fluorescence intensity [ 27 , 28 ], assuming that relatively lower fluorescence intensity correlates with fewer fibrils formed.…”
Section: Introductionmentioning
confidence: 99%